Severe Ovarian Hyperstimulation Syndrome despite low dose stimulation in Polycystic Ovarian Syndrome - Manappallil, Robin George; Kokoori, Sivadas Vilakupadath; Valsala, Nandini (Asian Journal of Medical Sciences, 2019)
Ovarian hyperstimulation syndrome (OHSS) is an iatrogenic complication of assisted reproduction technology. There is cystic enlargement of the ovaries along with fluid shift from the intravascular compartment to the third space due to increased capillary permeability and ovarian neoangiogenesis. Severe OHSS is uncommon and the condition can be fatal. Low-dose gonadotropin protocols have been introduced to reduce the risk of OHSS in patients with polycystic ovary syndrome (PCOS). The patient being reported had PCOS and developed severe OHSS despite low dose gonadotropin stimulation; which is a rare scenario.